PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA INKOFFIE SIDOARJO DENGAN PROMOSI SEBAGAI VARIABEL INTERVENING - Nuriyono Nuriyono; Tin Agustina; Ike Kusdyah (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2023)
Research aimed at knowing the effect of product quality, price and promotion factors that influence purchasing decisions in INKOFFIE Sidoarjo. The population used by most of the consumers of INKOFFIE Sidoarjo with a total sample of 100 respondents. Where sampling used purposive sampling method using the Smart PLS 3.0 program. The research of conclusion that is magnitude of the effect of product quality on promotion are 0.704. The magnitude of the effect of price on promotion are 0.216. The magnitude of the influence between promotions on purchasing decisions are 0.381. The magnitude of the influence of product quality on purchasing decisions which is 0.189. The magnitude of the influence of price on purchasing decisions are 0.434. The magnitude of the influence of product quality on purchasing decisions through promotions are 0.268. The magnitude of the influence of price on purchasing decisions through promotions are 0.082. This study explains that there is a positive and significant influence by product quality, price, and promotion on purchasing decisions directly or indirectly on INKOFFIE Sidoarjo consumers